Peran Guru Sekolah Dasar Dalam Pelaksanaan Proyek Penguatan Profil Pelajar Pancasila - Erwin Badateng (Universitas Negeri Makassar, 2023)
Abstract, In order to achieve national education goals, one of the steps taken by the government is to implement an independent curriculum in which there is a project to strengthen the profile of Pancasila students. This paper seeks to explain the concept and technique of the teacher's role in carrying out projects to strengthen the profile of Pancasila students and to discuss further about the competencies that teachers need to have in order to realize the project to strengthen the profile of Pancasila students, especially teachers who work in elementary schools that have not yet implemented the independent curriculum. The method uses a qualitative approach. The implementation procedure carried out is to find the type of literature needed both written and unwritten then review and present it. The data collection method used in this paper is from a literature study design. From the results of the discussion, it can be concluded that the teacher's role in actualizing the project to strengthen the Pancasila student profile is very vital, because in all activities from the beginning to the end of the project, the teacher plays an important role. Teachers must also involve students, so students can experience interactive and exploratory project activities. To support project implementation, teachers must have competencies that are reviewed from various perspectives. First, teacher competence in the context of policy, competence in teaching, competence to build students' strengths. For teachers who work in schools that have not yet implemented an independent curriculum and wish to implement an independent curriculum, they can use the 6 strategies provided by the government.